Opioid neurotoxicity: A case series and review from members of the Child Neurology Society Neurocritical Care Special Interest Group - Varina L. Boerwinkle; Imani H. Sweatt; Aniela Grzezulkowska; William R. Reuther; Aaron Gelinne; Emilio G. Cediel; Divakar S. Mithal; Carolyn S. Quinsey; Scott W. Elton (Wiley, 2024)
Abstract Objective The Child Neurology Society 2023 Annual Meeting Neurocritical Care Special Interest Group discussed pediatric opioid use-associated neurotoxicity with cerebellar edema (POUNCE). Inspired by the discussion and the suspicion of an underrecognized severe form of the disorder, we provide a case series and literature review on this important and emerging topic. Methods The meeting was moderated by coauthor DSM, with formal presentation by coauthor AG, and supplemented with a supporting case by coauthor VLB. The attendees, by show of hand, were queried for experience with direct care of children in the critical care unit with neurotoxicity from opioid exposure. These meeting elements informed our literature review and case series. Results A key focus of the meeting was the importance of interdisciplinary communication regarding POUNCE, emphasizing the necessity for neurosurgical assessment due to mass effect. Approximately 10 of 40 attendees, representing different US hospitals, reported caring for children with opioid neurotoxicity and concern for increased intracranial pressure. Described during the meeting was a 2‐year‐old girl with opioid exposure, rapidly worsening neurological exam, and transforaminal herniation concerning for severe POUNCE syndrome and impact on brain networks by resting‐state functional magnetic resonanance imaging (rs‐MRI). After surgical decompression did not improve her neurological function, she underwent rs‐MRI, electroencephalogram, and MRI. The networks indicated better neurological function than the exam, consistent with outcome. In contrast, the second patient, was an 11‐month‐old boy with fentanyl exposure who was treated for opioid overdose and closely monitored clinically. He did not require surgical intervention and has recovered well. Interpretation These patients add to the few publications documenting the management of POUNCE, which may require urgent posterior cranial fossa decompression, and highlight the potential for good outcomes. Additionally, this is the first report documenting rs‐fMRI for this condition, which was consistent with the patient's outcome.